Morphological and Nutritional Properties of Moroccan Capparis spinosa Seeds - Nidal El amri; Faouzi Errachidi; Abdellatif Bour; Sara Bouhaddaoui; Rachida Chabir (The Scientific World Journal)
Capparis spinosa is one of the few shrub species which has so many qualities with many uses. In this case, the present work aimed to study both some morphological characteristics and biochemical components (proteins, lipids, and carotenoids) of fresh C. spinosa seeds with three different sizes, collected from two Moroccan regions. In this study, C. spinosa seeds present a total of proteins ranging from 23.32 to 28.5% on a dry weight basis. Additionally, the total lipids varied between 2.8 and 3.4%. C. spinosa seeds contained a high level of carotenoids. Besides, the analytical values have been variously affected by both size and location. Further, the preliminary morphological and anatomical characterization of leaves, stems, and morphological properties such as length, width, thickness, geometric mean diameter, sphericity, surface area, and mass of 100 seeds have been determined. Consequently, this present study confirms the importance of Moroccan C. spinosa seeds, which represent a significant nutritional value. Also, its good morphological quality is a significant indicator of commercial criteria.